Factors influencing the adoption of HIV prevention measures in low socio-economic communities of inner-city Durban, South Africa - Firoza Haffejee; Jennifer Ducray; Jyotika Basdav; Colette Kell (Taylor & Francis Group, 2023)
ABSTRACTSouth Africa is the epicentre of the HIV pandemic. Although there have been health promotion education campaigns to reduce HIV incidence, these have not achieved the desired outcomes. When exploring the effectiveness of these campaigns, it is useful not only to examine HIV knowledge, but also to explore the relationship between that knowledge and health-related behaviour. This study aimed to determine the (1) level of knowledge of HIV prevention, (2) relationship between the level of knowledge and the adoption of these behaviours and (3) barriers to sexual behaviour change of vulnerable women in Durban's city centre, KwaZulu-Natal, South Africa. A mixed methods approach was used to collect information from a marginalised population of women (n = 109) attending a non-governmental organisation, which provides for the needs of people from low socio-economic strata. Data were collected during September 2018 at a wellness day programme at the centre. A total of 109 women, over the age of 18 years answered the questionnaire. Knowledge of HIV transmission was high, with majority of participants correctly identifying modes of transmission. Almost all the participants (91.2%) had been tested for HIV, with 68.8% tested a minimum of three times. Despite this, sexual risk behaviour was high. Despite the high level of knowledge of HIV transmission, there was no relationship between HIV knowledge and adoption of behaviours for the prevention of HIV transmission (p = .457). However, bivariate analysis showed an association between transactional sex and living in informal housing (OR = 31.94, 95% CI: 5.65-180.63, p < .001). Living in informal housing was also associated with having multiple current sexual partners (OR = 6.30, 95% CI: 1.39-28.42, p = .02). Multivariate analysis, after adjusting for all other factors, indicated that the odds of having transactional sex was increased by 23 times in those who did not have formal housing (OR = 23.306, 95% CI: 3.97-144.59, p = .001). Qualitative responses showed that women perceived poverty as the overarching factor determining the lifestyle choices which impacted their health. They indicated a need for employment opportunities and provision of housing to alleviate both poverty as well as transactional sex. Although, participants from this study understood the benefits of the protective behaviours to prevent HIV transmission, economic and social factors do not afford this vulnerable group the opportunity nor the motivation to adopt such behaviours. In the current climate of increasing unemployment and escalating GBV, urgent interventions are needed in terms of employment opportunities and empowerment drives to prevent an increase in HIV transmission.